Open Journal Systems: results after the implementation of video tutorials as initiative for the editing process in a journal - Luisa Acosta Ortega; Xiomara Cascaret Soto; María Elena Pardo Gómez; José Manuel Izquierdo Lao; Héctor Luis Mustelier Ferrer (Centro Provincial de Información de Ciencias Médicas, 2019)
In this article the results obtained when corroborating the feasibility of the elaborated and implemented video tutorials, as support material to achieve the correct use of the Open Journal Systems platform in the journal MEDISAN are analyzed. Also, the real factors that still impact on the flow of all the stages of the editing process and the actors in each of them are investigated; also, recommendations are made on how to socialize the videos, once they are at the disposal of the authors and reviewers community and for the rest of the professionals who need to interact in this platform for the publishing process of an electronic journal.